Formulas and calculations for drilling, production and workover. - Lapeyrouse, Norton J. (Gulf Professional, 2011)
A quick reference for day-to-day work out on the rig or a handy study guide for drilling and well control certification courses, Formulas and Calculations for Drilling, Production and Workover has served a generation of oilfield professionals throughout their careers. Compact and readable, Formulas and Calculations for Drilling, Production and Workover, 3rd Edition is a problem solving time saving tool for the most basic or complex predicaments encountered in the field. All formulas and calculations are presented in easy-to-use, step-by-step order, virtually all the mathematics required out on the drilling rig is here in one convenient source, including formulas for pressure gradient, specific gravity, pump output, annular velocity, buoyancy factor, volume and stroke, slug weight, drill string design, cementing, depth of washout, bulk density of cuttings, and stuck pipe. The most complete manual of its kind, Formulas and Calculations for Drilling, Production and Workover, 3rd Edition features 30% new information, including case studies and basis simulations equations. The third edition of this best selling book also includes computational tools and techniques for: unbalanced drilling, horizontal directional and air and gas drilling operations, evaluate ESP performance of wells, design / redesign ESP and recommend changes to improve well's operation, handle special production projects including production string designs for new wells, evaluation of new production methods, scaling in well bores and any other project affecting the operation of Amal area wells. Back-of-the envelope calculations that save time and money Easily evaluate the performance of your well Confidently design or redesign operations that will improve production Handle special production projects with ease.